Peningkatan Peran Perbankan Syariah dalam Pengembangan Industri Makanan Halal di Indonesia - Sari, Lili Puspita (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The halal food industry is one of the sub-sectors in the halal ecosystem which has considerable potential in Indonesia. However, the role of Islamic banking in supporting the development of this sector is still not optimal, especially financing. This study aims to provide alternatives in terms of contracts and financing models that can support Islamic bank financing in the industry. Then can affect increase the role of Islamic banks to support halal food industry in Indonesia. This research is a library research with a qualitative descriptive approach with content analysis techniques. The results show that the role of Islamic banking is currently still minimal in supporting the halal food industry in Indonesia, especially in terms of financing. In terms of financing models, partnership / synergy and community financing models can be alternatives in the agricultural sector. Meanwhile, the linkage and ecosystem-based financing model is suitable to be applied to the food and beverage processing and service industry sectors.